2020
DOI: 10.3892/ol.2020.12238
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative plus postoperative neutrophil‑lymphocyte ratio for predicting overall survival following partial hepatectomy for hepatocellular carcinoma

Abstract: The preoperative neutrophil-lymphocyte ratio (NLR) and the postoperative NLR have been reported to be prognostic factors for malignant tumors. However, the prognostic value of combining the preoperative NLR and postoperative NLR for hepatocellular carcinoma (HCC) remains unclear. In the present study, a cohort of 70 patients with primary HCC were retrospectively reviewed. The optimal cut-offs for continuous variables were determined by the maximally selected rank statistics. The prognostic factors included pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Further analysis found that there was no correlation between clinicopathological indicators including tumor stage and postNLR. Our previous study found that the preoperative inflammatory indicators were related to tumor burden such as tumor size, while the preoperative tumor burden was not correlated with postoperative inflammatory indicators [38]. The possible reason was that after the primary tumor burden was removed, the host's immune response has changed [39].…”
Section: Discussionmentioning
confidence: 97%
“…Further analysis found that there was no correlation between clinicopathological indicators including tumor stage and postNLR. Our previous study found that the preoperative inflammatory indicators were related to tumor burden such as tumor size, while the preoperative tumor burden was not correlated with postoperative inflammatory indicators [38]. The possible reason was that after the primary tumor burden was removed, the host's immune response has changed [39].…”
Section: Discussionmentioning
confidence: 97%
“… 14 Our previous study confirmed this finding and revealed that a high preNLR was associated with a greater tumor burden, but there was no significant correlation between the postNLR and tumor burden. 15 Tumor recurrence is affected by many factors. Even after the HCC tumor is completely removed or ablated, the microenvironment of the remaining carcinogenic tissue in the liver can also cause recurrence of de novo HCC tumors.…”
Section: Discussionmentioning
confidence: 99%
“… 8–13 However, the treatment process for tumors is complicated and long, and we should not only pay attention to the influence of preoperative indicators on the prognosis of HCC but also to postoperative indicators. Previous studies showed that the immune status of HCC patients changed after the primary tumor burden was reduced, 14 , 15 and a high postNLR was associated with poor long-term prognosis. 16 , 17 However, the value of many postoperative inflammatory indicators was not clarified.…”
Section: Introductionmentioning
confidence: 99%
“… 32 Furthermore, both pre- and postoperative NLR can predict the rate of all-cause mortality in patients with hepatocellular carcinoma after partial hepatectomy. 33 On the other hand, they may be also applied for estimating the current activity and predicting the prognosis of chronic inflammatory diseases. NLR above the optimal cut-off value was proposed as a determining factor for the current active systemic lupus erythematosus.…”
Section: Applying Serologic Indices To Clinical Use In Rheumatic Disementioning
confidence: 99%